2003
DOI: 10.1002/ptr.1291
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of extracts from Alpinia katsumadai seed

Abstract: Alpinia katsumadai (Zingiberaceae) has been widely used in traditional Chinese medicine to treat a variety of conditions such as emesis and gastric disorders. However, very little is known about the cellular actions by which this plant mediates its therapeutic effects. Various aspects of antioxidant activity were evaluated in a total extract derived from Alpinia katsumadai seed in this study. Relatively high levels of 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity were detected in the total e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 36 publications
(24 reference statements)
1
78
0
1
Order By: Relevance
“…In the presence of only H 2 O 2 (control), cell death ratio reached up to 70% after 45 min of the treatment ( Figure 3). As compared with the control, the reduction of cell death was observed after the treatment of each antioxidant at 20 and 50 毺 g/mL concentration. We estimated enrichment factor to detect nucleosomal damage, a quantitative measurement of apoptosis (cell death detection), which was carried out by ELISA.…”
Section: Cytoprotectivity (Cell Viability)mentioning
confidence: 88%
See 4 more Smart Citations
“…In the presence of only H 2 O 2 (control), cell death ratio reached up to 70% after 45 min of the treatment ( Figure 3). As compared with the control, the reduction of cell death was observed after the treatment of each antioxidant at 20 and 50 毺 g/mL concentration. We estimated enrichment factor to detect nucleosomal damage, a quantitative measurement of apoptosis (cell death detection), which was carried out by ELISA.…”
Section: Cytoprotectivity (Cell Viability)mentioning
confidence: 88%
“…Thereafter, cells become resistant to oxidant and oxidant-induced apoptosis [24] . Results (Figure 7,8) indicated that antioxidants (SA, AA, CA and 毩-TA) treated at both concentrations 20 and 50 毺 g/mL to cell lines for 18 h significantly protected the bcl-2 levels. Additionally, only H 2 O 2 treatment (vegative control) for 2 h significantly reduced the bcl-2 levels as compared with positive control RCC-26 cell lines.…”
Section: Effect Of Antioxidants On Bcl-2 Levelmentioning
confidence: 96%
See 3 more Smart Citations